Separable representations for finite-range potentials - Bund, G. W.; Tijero, M. C. (Springer Nature, 1980)
Separable EST expansions of potentials which vanish outside a certain radius are studied by using as a basis complete sets of eigenfunctions obtained by applying appropriate boundary conditions. The method is applied to the square well, the convergence of the T-matrix being obtained with four terms in the basis. © 1980 Società Italiana di Fisica.